Key Components of Store-Operated Ca2+ Entry in Non-Excitable Cells - Yosuke Tojyo; Takao Morita; Akihiro Nezu; Akihiko Tanimura (Elsevier, 2014)
Abstract.: Store-operated Ca2+ entry (SOCE) is a ubiquitous Ca2+ entry pathway in non-excitable cells. It is activated by the depletion of Ca2+ from intracellular Ca2+ stores, notably the endoplasmic reticulum (ER). In the past 9 years, it has been established that two key proteins, stromal interacting molecule 1 (STIM1) and Orai1, play critical roles in SOCE. STIM1 is a single-pass transmembrane protein located predominantly in the ER that serves as a Ca2+ sensor within the ER, while Orai1 is a tetraspanning plasma membrane (PM) protein that functions as the pore-forming subunit of store-operated Ca2+ channels. A decrease in the ER Ca2+ concentration induces translocation of STIM1 into puncta close to the PM. STIM1 oligomers directly interact with Orai1 channels and activates them. This review summarizes the molecular basis of the interaction between STIM1 and Orai1 in SOCE. Further, we describe current findings on additional regulatory proteins, such as Ca2+ release-activated Ca2+ regulator 2A and septin, novel roles of STIM1, and modulation of SOCE by protein phosphorylation. Keywords:: store-operated Ca2+ entry, STIM1, Orai1, calcium channel